Accountability in Campaign Finance Audits: A Phenomenological Study of Auditor in Indonesian Regional - Muhammad Arsyad; Alimuddin Alimuddin; Syarifuddin Syarifuddin (CV. Global Cendekia Inti, 2026)
This study addresses the gap between formal regulatory compliance and substantive accountability in campaign finance audits in regional elections. Despite regulations emphasizing transparency, campaign finance audits often fail to ensure the accuracy and integrity of financial reporting, raising concerns about their effectiveness in supporting democratic governance. This study aims to explore how auditors interpret and construct accountability in campaign finance audits. A qualitative phenomenological approach was employed to capture auditors lived experiences. Data were collected through semi-structured interviews with auditors from public accounting firms involved in the 2024 regional elections in Indonesia and analyzed using phenomenological procedures, including thematic clustering and meaning interpretation. The findings reveal that campaign finance audits are better understood as legitimacy seeking mechanisms than as tools of substantive accountability. Five themes emerged, indicating that audits function mainly as legitimacy-seeking mechanisms rather than instruments of transparency. This study contributes by introducing “symbolic accountability” and highlighting the need to strengthen enforcement and expand audit scope.